International Food Policy Research Institute (IFPRI) Intellectual Property (IP) policy - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
The International Food Policy Research Institute (IFPRI) is committed to ensuring that Intellectual Property (IP) originating from its research activities is used in support of its vision of a world free of hunger and malnutrition, and in accordance with legal obligations, for the benefit of society, the IP Creators, and the Institute. In pursuit of its mandate to provide research-based policy solutions to sustainably reduce poverty and end hunger and malnutrition in developing countries, staff at IFPRI generate a wide range of IP including a) publications, b) datasets, c) databases, d) software, application, and source codes, e) audio, video, and images, f) methods, tools and models, g) technologies, h) websites and web services, and i) inventions. The IP generated may be subject to different forms of Intellectual Property Rights (IPR) protection arising out of various relevant jurisdictions around the world.